Acquiring electronic databases in school library (2011)
"This article examined how electronic databases could be used to enrich curriculum delivery in Nigerian schools. Some of features of electronic databases were discussed in the article and the potentials of free websites were also examined. A number of free electronic databases were also listed for use by schools and School Library Media Centers. The article recommended that School Library Media Centers should be adequately funded by the government and private school owners to facilitate the use of electronic databases. In addition, Nigerian School Library Media Specialists would be able to maintain a virtual library presence through links to free database resources and selected Internet portals when adequately funded. "